Assessment of a solar PV-driven desiccant-based air handling unit with different tracking systems. (August 2019) - Roselli, C.; Sasso, M.; Tariello, F.
Highlights: A PV plant coupled with a desiccant based air handling unit is considered. Effects of four solar tracker on energy and environmental performance are analyzed. Energy and environmental benefits increase with PV field peak power. Dynamic simulations are performed to carry out energy and environmental analyses. Interactions with the grid are enhanced by the PV capacity and production increase. Abstract: In this paper a solar electric heating and cooling system consisting of a photovoltaic plant and an air handling unit equipped with desiccant wheel is analysed. The dehumidification of process air supplied to a conditioned room is achieved by means of the desiccant wheel that is filled with a hygroscopic material instead of throughout a cooling dehumidification as it happens in standard air handling units. The desiccant wheel regeneration, for a continuous operation, is obtained by using the electricity available from the solar plant in an electric heater. Dynamic simulation have been carried out to compare this innovative system with a conventional one for a year of operation, considering that it serves a university classroom of 63.5 m 2 located in Benevento. Primary energy saving and equivalent CO2 emission reduction are estimated as a function of photovoltaic plant peak power and panels tilt angle. The proposed solution demonstrates to be very interesting for an energy and environmental point of view, reaching maximum energy saving and emission reduction over 79%. Optionally four different tracking systems were simulate for solar field. The two-axis tracker achieves the best energy and environmental performance but it has the worst behaviour considering the interaction with the power grid.